Land-use conversion and rural income dynamics in rubber to oil palm transition in Riau Province, Indonesia, using a PSM-DID approach - HEFFI CHRISTYA RAHAYU; ETTY PUJI LESTARI; AHMAD FATHONI; FEBIANA GITYA (Asian Journal of Agriculture, 2026)
Abstract. Rahayu HC, Lestari EP, Fathoni A, Gitya F. 2026. Land-use conversion and rural income dynamics in rubber to oil palm transition in Riau Province, Indonesia, using a PSM-DID approach. Asian J Agric 10 (1): g100178. https://doi.org/10.13057/asianjagric/g100178. The prolonged decline in rubber prices has prompted farmers to shift their land to oil palm cultivation, despite its challenges (e.g., replanting requirements and price volatility). However, there is limited research on smallholder farmers, a vulnerable group that is often overlooked by the law. Therefore, this study attempts to fill the gaps by examining the causal effect of rubber to oil palm land conversion on annual household income among smallholder farmers in Riau Province, Indonesia. We observed and interviewed 206 farmers in Kampar and Rokan Hulu regencies in 2023-2024, and analysed the data using a Propensity Score Matching-Difference-in-Differences (PSM-DID) approach. For the analysis, the study period was divided into two phases: the pre-conversion period (around 2015, before the decline in rubber prices) and the post-conversion period (2021-2022). Propensity score matching was used prior to the DID analysis to ensure that the treatment and control groups were more comparable. The results show that households that converted their land from rubber to oil palm earned significantly higher incomes than comparable households that did not convert. On average, household income increased by approximately 38.5% following conversion. The results indicate that land conversion can bring substantial economic benefits to smallholders. At the same time, policymakers need to consider the environmental costs that may accompany these gains.